Exploring the Limiting Open‐Circuit Voltage and the Voltage Loss Mechanism in Planar CH3NH3PbBr3 Perovskite Solar Cells. Issue 18 (22nd June 2016) - Chen, Shi; Hou, Yi; Chen, Haiwei; Richter, Moses; Guo, Fei; Kahmann, Simon; Tang, Xiaofeng; Stubhan, Tobias; Zhang, Hong; Li, Ning; Gasparini, Nicola; Quiroz, Cesar Omar Ramirez; et al.
Abstract : Perovskite solar cells based on CH3 NH3 PbBr3 with a band gap of 2.3 eV are attracting intense research interests due to their high open‐circuit voltage ( V oc ) potential, which is specifically relevant for the use in tandem configuration or spectral splitting. Many efforts have been performed to optimize the V oc of CH3 NH3 PbBr3 solar cells; however, the limiting V oc (namely, radiative V oc : V oc, rad ) and the corresponding Δ V oc (the difference between V oc, rad and V oc ) mechanism are still unknown. Here, the average V oc of 1.50 V with the maximum value of 1.53 V at room temperature is achieved for a CH3 NH3 PbBr3 solar cell. External quantum efficiency measurements with electroluminescence spectroscopy determine the V oc, rad of CH3 NH3 PbBr3 cells with 1.95 V and a Δ V oc of 0.45 V at 295 K. When the temperature declines from 295 to 200 K, the obtained V oc remains comparably stable in the vicinity of 1.5 V while the corresponding Δ V oc values show a more significant increase. Our findings suggest that the V oc of CH3 NH3 PbBr3 cells is primarily limited by the interface losses induced by the charge extraction layer rather than by bulk dominated recombination losses. These findings are important for developing strategies how to further enhance the V oc of CH3 NH3 PbBr3 ‐based solar cells. Abstract : CH3 NH3 PbBr3 solar cells with the average open circuit voltage of 1.50 V are achieved . External quantum efficiency measurements and electroluminescence spectroscopy are employed to predict the limiting open circuit voltage and the corresponding voltage loss mechanism are clarified via temperature dependent measurements, beneficial for further open circuit voltage improvements of CH3 NH3 PbBr3 solar cells.